Grinning at horrors: gender and visual triumphalism. Issue 3 (2nd October 2021) - Herzog, Omri; Yaron, Idan
Abstract: This article offers a reading of visually and ethically disturbing images, published over the past two decades, that have earned far-reaching exposure: photographs of male and female soldiers grin as they observe horrific sights. In most cases, these images, uploaded to social media, sparked a heated international debate. Perhaps more than other visual elements in these photos, it was the female soldiers' smiles against the backdrop of atrocities that gained a greater presence in the eye of the media storm that had ensued, earning far more attention than the smiles of the soldiers' male counterparts. Indeed, this visual imagery directly indicates the construction of femininity and masculinity within militaristic-cultural contexts and dictates its own ideological perceptions and moral judgments. A reading of the smile's meanings in this context raises issues connected to the anthropology of physical gestures and the theory of photography, as well as to current ideological-ethical issues. This article comprises three pivotal interpretations, and while each framework construes the meaning of the smile in its own way, gendered visual literacy underlies all of them. By using this case study in order to point to visual literacy's seminal role in critical interpretation, we aim to demonstrate the cruciality of feminist visual literacy in a multi-dimensional analysis of visual imagery.